O enquadramento jornalístico das matérias de violência contra a mulher e o trabalho das jornalistas da Gazeta ES - Lopes, Yara Karolinne Sousa (2021)
This research brings a discussion about what the brasilian press presents in the articles of violence against woman, observing the framings that are made. The intention was to analyze the content, in orther to understand if talk about the issue already means a victory to the gender's battle, with a disruption of the sexist, patriarchal e misoginist hegemony that is present on our society in a capitalist context, or if the articles actually bring a mainteinence of the status quo. We also tried to understand how is done the work of the woman who creat this type of content to see both sides of this history and conclude a whole comprehension of the results tha arrive to the public, and for that, we made interviews with reporters who work and worked in the paper. Therefore, we analysed 20 articles of the Gazeta, 12 from 2019, the majority in the policy editorial, e 8 in a news editorial made by the paper and called Todas Elas, that the company announced that had the goal to do a differeent approach on the gender's matter. To arrive in this comprehension, we first made a panamora about journalism, power, hegemony e counter-hegemony in the capitalit society, using Genro Filho (2012), Moraes (2018), Kohan (2001) e Coutinho (2008). We used Entman (1993) to analyse the articles with framing. To discuss gender, we used authors such as Davis (2016) and Gago (2020). To discuss gender and labor, we used Marx (2017) and Fígaro (2015). With the news faming analysis and the enterviews with the womans, we noticed that there is still the reoproduction of sexists, racists e classists signs on the articles about gender violence, but that those are results of the papeer's interest and the socialization tha of the people, including the workers. But even with this result, it's posible to believe em news paths and possibilities of producing a diferente and transforming content.